1973
DOI: 10.1111/j.1749-6632.1973.tb28287.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein and Ribonucleic Acid Metabolism in Brains of Mice Following Chronic Alcohol Consumption*

Abstract: In these proceedings there has been a great deal about the effects of alcohol on biogenic amine metabolism and the possible role of biogenic amine condensation products in alcoholism. There has been little mention of how alcohol affects macromolecules, and indeed the literature is scanty in this problem area. The present report will deal with alterations in brain protein and nucleic acid metabolism as a function of chronic alcohol ingestion in the C57BL/6J mouse. Much of what will be discussed has appeared in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Posttranslational modifications of histone amino-termini, such as acetylation, phosphorylation and methylation are in most cases correlated with functional organization of chromosomes and chromatin dynamics (Kohlmaier et al, 2004;Jenuwein and Allis, 2001;Wilkins, 2005). An in vivo study on cell morphology reported that the size and shape of alcohol fed hepatocytes were reduced substantially relative to untreated cells (Noble and Tewari, 1973). Initially, it was reported that chromosomes of chronic alcohol treated hepatocytes have highly condensed and altered nonhistone nuclear proteins that may contribute as epigenetic signals (Mahadev and Vemuri, 1998;Park et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Posttranslational modifications of histone amino-termini, such as acetylation, phosphorylation and methylation are in most cases correlated with functional organization of chromosomes and chromatin dynamics (Kohlmaier et al, 2004;Jenuwein and Allis, 2001;Wilkins, 2005). An in vivo study on cell morphology reported that the size and shape of alcohol fed hepatocytes were reduced substantially relative to untreated cells (Noble and Tewari, 1973). Initially, it was reported that chromosomes of chronic alcohol treated hepatocytes have highly condensed and altered nonhistone nuclear proteins that may contribute as epigenetic signals (Mahadev and Vemuri, 1998;Park et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, altered activity of any of the enzymes or substrates involved in the addition of the carbohydrate constituents to the polypeptide backbones could result in an abnormal synthesis o f fucosylated SPM glycoproteins. Nonetheless, it should be noted that the effects observed in the present study are not directly due to the depressant effect of ethanol (or acetaldehyde) on protein synthesis [Tewari and Noble, 1971;Noble and Tewari, 1973;Renis et al, 19751 or on glycoprotein synthesis or secretion [Sorrell et al, 1977;Sorrell and Tuma, 1978;Tuma and Sorrell, 19811. Whereas the presence of ethanol (or acetaldehyde) in vitro or in vivo reportedly has the mentioned effects, little information is available about protein or glycoprotein synthesis one or more weeks aftcr the last exposure to ethanol.…”
Section: Discussionmentioning
confidence: 85%
“…How brain volume is restored by abstinence re mains uncertain. Increases in blood flow and blood volume are certainly one factor, but other possibili ties include regeneration of attenuated neuronal processes and reversal of inhibited protein syn thesis (Noble and Tewari, 1973;Te wari et aI. , 1978;Walker et aI.…”
Section: Discussion Brain Volume Measurements In Chronic Alcoholic Pamentioning
confidence: 99%